Pengembangan Sumber Daya Air Di Pulau – Ende Kabupaten Ende - Tan, Valentinus (TEKNOSIAR, 2022)
It is very important to develop water resources in the Ende islands, Ende Regency, NTT, especially regarding the fulfillment of the population's clean water needs, which currently tend to be inadequate. The survey results show that the source of clean water for the population to meet the needs of MCK and drinking water is from Shallow Wells and Rainwater Storage (PAH). Meanwhile, based on the results of the research, it shows that both the quantity and quality of water from these two sources are inadequate and good. So it is necessary to develop and improve clean water facilities and infrastructure, including improving the quality of drinking water for the population. The study of the development of water resources in this area resulted in several related suggestions, namely in this area it is necessary to build a surface water catchment building with a reinforced concrete pool. This building is to serve the provision of clean water for residents on the ridge and in the western foothills. Recommended building locations around the valley/ridge east of the island. Other shallow wells scattered in the settlements cannot be used for clean water because their hardness is high so they are not suitable for drinking. And one Osmosis water management unit is no longer functioning.